PENERAPAN SISTEM PEMBERIAN REWARD PADA HOTEL INNA GRAND BALI BEACH - Ni Ketut Narti; Ni Ketut Lasmini; Lily Marheni; Ni Komang Suci Martini (Forum Manajemen STIMI Handayani Denpasar, 2019)
The purpose of this research is to know the application of reward system at Hotel Inna Grand Bali Beach. The object of research is the implementation of reward system using qualitative and qualitative descriptive approach. Data collection in this research is interview observation, and literature research.The results showed that at Hotel Inna Grand Bali Beach there are 4 types of rewards that are used to motivate employee performance: Reward Incentives, Reward Production Premium, Reward Best Employee, Reward Period. The application of the reward system of each type varies - based on SKD (Directors' Decree) and the basis of reward. Providing incentive rewards based on employee attendance. Reward of production premium based on company productivity. Giving rewards best employee based on employee performance. Giving rewards for working period based on length of employee work. The initial process of checking employee data requires a lot of time making the application of rewards less effective and efficient. This is caused by the data of many employees and done in two checking process that is timekeeping and finger print so that require precision in process of checking data.